New Approaches to Inform, Motivate, and Advance Small and Mediums-scale Fish Farmers: Building Industry Capacity Through Cell Phone Networks, Training, and Market Participation - Molnar, Joseph J.; Matuha, Moureen; Boyd, Claude; Terhune, Jeff; Veverica, Karen; Walakira, John; Naigaga, Shamim; Hyuha, Theodora; Karuhanga, Monica (2National Fisheries Resources Research Institute, 2013)
Mobile phones can improve aquaculture productivity by increasing access to technical guidance, extension services, product assembly, input coordination, and price discovery for small- and mediumscale fish farmers. Data were obtained in five focused group interviews held across Uganda. The findings indicate that the use of mobile phones is common among fish farmers in Uganda. Majority of the farmers reported that their mobile phones were primarily used for purposes that improve social development and livelihoods. Many fish farmers report using mobile phones to acquire technical guidance, contact family members, and communicate with those who provide agricultural inputs and market information, which results into increased income. The study also highlighted that access to agricultural information has been widespread, but support is needed for disseminating information on market prices and fish production. At present, most farmers depend on the word of mouth to get information from extension officers and intermediary fish farmers, who are not always available when needed. Farmers prioritized information on pond management, feed broodstock and water quality management, stocking and harvesting, and, most importantly, market prices. Although farmers were also interested in other categories of information, such as fish diseases, seed variety, fish species to be cultured, etc., only a small sample prioritized them.
Keywords: Small and Mediums-scale Fish Farmers; Industry; Cell Phone Networks; Training